DEVELOPMENT AND SURVIVAL RATE OF GIANT SHRIMP LARVA (Macrobrachium rosebergii de Man) GIMacro II AT DIFFERENT SALINITIES - Deny Sapto Chondro Utomo; Wardiyanto Wardiyanto; Triando Kurniawan (Jurusan Perikanan dan Kelautan, 2018)
GIMacro II prawn larvae is able to grow well at a salinity of 8-15 ppt. This condition can be improved by improving the methods of adaptation to changes in salinity prawn larvae production activities, by determining the pattern of changes in salinity are right. Salinity media through osmotic pressure affect the physiological activity, where the cells in body organs prawns should be in liquid media with ionic composition and concentration of the same with the environment. Having obtained the optimum salinity on larval rearing prawns GIMacro II in different salinity media is expected to produce a population of prawns GIMacro II with superior durability specific to environmental conditions, which can then be directed to improve the utilization of marine resources to the salinity of the best. This research aims were to study the growth and survival of larvae prawns GIMacro II reared on media of different salinities. The study used completely randomized design with three treatments and three replications. The treatments were larval rearing prawns GIMacro II at different salinities (10 ppt, 12 ppt, and 14 ppt). The results showed that the culture of prawn larvae GIMacro II at different salinity affect significantly on growth and survival of larvae prawns GIMacro II. The highest development of GIMacro II prawn larvae obtained from 12 ppt salinity treatment (7.13 ± 0.03%) and the highest survival rate was obtained also from 12 ppt salinity treatment (67.67 ± 4.51%)